CURRENT PROBLEMS OF PLANTS IN THE AUTOMOTIVE INDUSTRY IN THE LIGHT OF KAZAKHSTANI AND INTERNATIONAL LAW - Sarsembayev, Марат Алдангорович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
This article is devoted to the analysis of the problems of the modern automotive industry and their solution through the norms of Kazakhstan and international law. The topic of the article is covered by the example of Kazakhstan, Russia and Uzbekistan, which are the most prominent automobile manufacturers in the entire CIS, by comparing their indicators and legal sources between them, by comparing their indicators with the world indicators of automobile production. To solve the problems of the automotive industry, the author of the article proposes to quickly adopt a new law on industrial policy not only in Kazakhstan, but also in other countries related to industrialization, including the automotive industry. By adopting such a law, the country gets an idea of the vector of its autoindustrial movement. Another problem that needs to be solved is the need to introduce digitalization in the automotive industry, which can be solved by adopting the law of the same name, as well as by concluding interstate agreements with developed countries on the transfer of experience in digitizing automotive production in Kazakhstan and other countries. Since in Uzbekistan, Kazakhstan and a number of other countries, automobile production is based on industrial assembly, the problem of expanding localization (local content) in the automotive industry and in related industries of the country arises in full growth. The solution to this problem is possible on the basis of the law on localization, interstate agreements on cooperation with developed countries on sending their specialists for training in these states on the spot. The problems of the automotive industry in the article are shown in conjunction with the requirements of the fourth industrial revolution, showing promising ways of developing the automotive industry along the path of digitalization, robotization, automation of automotive production based on artificial intelligence.